2017
DOI: 10.1111/hiv.12563
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and progression of carotid intima‐media thickness in HIV‐positive Canadians

Abstract: Baseline 25(OH)D was associated with CIMT progression in this relatively vitamin D replete, predominately white and male, Canadian HIV-positive population. Future research needs to establish causality as this may warrant more targeted screening or supplementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
(66 reference statements)
1
4
0
Order By: Relevance
“…In those with type 1 diabetes mellitus with mean age around 30–35 years old, previous studies have reported no significant association between the circulating serum 25(OH)D concentration and cIMT 24 , 25 . In a cross-sectional cohort study of 654 relatively healthy participants without history of coronary heart disease, serum 25(OH)D concentration was significantly inversely related to the internal cIMT but not the common cIMT 26 and similar finding was found in another study composed of HIV-infected patients 27 .…”
Section: Discussionsupporting
confidence: 74%
“…In those with type 1 diabetes mellitus with mean age around 30–35 years old, previous studies have reported no significant association between the circulating serum 25(OH)D concentration and cIMT 24 , 25 . In a cross-sectional cohort study of 654 relatively healthy participants without history of coronary heart disease, serum 25(OH)D concentration was significantly inversely related to the internal cIMT but not the common cIMT 26 and similar finding was found in another study composed of HIV-infected patients 27 .…”
Section: Discussionsupporting
confidence: 74%
“…Study participants were enrolled as part of the Canadian HIV-Vascular Study, which was a 5-year multi-center cohort study that has been previously published [30]. The population consisted of adults diagnosed with HIV, aged 35 years or older, presenting for routine clinical visits at one of five participating HIV clinics.…”
Section: Methodsmentioning
confidence: 99%
“…One study found that 44.6% of their HIV participants had vitamin D deficiency [21], while another study reports that the numbers vary from 24% to 72% depending on climate, age, and geographic area [20]. There have been observational studies that show an association between low vitamin D levels and increased cardiovascular disease [22]. Further investigations show an inverse relationship between carotid media-intima thickness (CMIT), a measure of subclinical vascular disease, and vitamin D levels in HIV patients [22].…”
Section: Micronutrient Supplementationmentioning
confidence: 99%
“…There have been observational studies that show an association between low vitamin D levels and increased cardiovascular disease [22]. Further investigations show an inverse relationship between carotid media-intima thickness (CMIT), a measure of subclinical vascular disease, and vitamin D levels in HIV patients [22]. There was also an association with low vitamin D levels and subclinical atherosclerosis when compared to HIV patients without deficient vitamin D levels [21].…”
Section: Micronutrient Supplementationmentioning
confidence: 99%